2018
DOI: 10.25301/jpda.274.160
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Palatally Impacted Canines and Sella Turcica Bridging

Abstract: To investigate the association between palatal canines and sella bridging as well as to establish the type of calcification of sella common to subjects with impacted canines. METHODOLOGY: The sample included male and female patients aged above 12 years, presenting to the orthodontic OPD of Bahria University Medical and Dental College for fixed or removable orthodontic treatment the sample was 105 divided into subjects (34) and control (71) groups. The control group included patients having normally erupted can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The difference was higher in males. A higher length in subjects with PCI is inconsistent with data reported in previous studies [14,15,23,25]. An in-depth review of the studies revealed that their results differed from each other in terms of length, even in the controls.…”
Section: Sella Turcica Dimensionscontrasting
confidence: 72%
See 4 more Smart Citations
“…The difference was higher in males. A higher length in subjects with PCI is inconsistent with data reported in previous studies [14,15,23,25]. An in-depth review of the studies revealed that their results differed from each other in terms of length, even in the controls.…”
Section: Sella Turcica Dimensionscontrasting
confidence: 72%
“…All the authors who studied canine impaction used the method proposed by Leonardi et al [19], which involves the sella length-todiameter ratio (method 1). Except for the study by Majeed et al [14], the prevalence of partial bridging was higher in subjects with impacted canines. The difference was statistically significant in seven studies [12,13,16,19,[22][23][24] and insignificant in two studies [14,17].…”
Section: Sella Turcica Bridgingmentioning
confidence: 74%
See 3 more Smart Citations